Analisis Maksim Kesantunan dalam Podcast Deddy Corbuzier Bersama Rafael Smash - Hilmi Alfianti (Inovasi Pendidikan dan Anak Usia Dini, 2024)
This study is based on politeness in language in Deddy Corbuzier's podcast with Rafael Smash entitled "Rafael Seblak, Don't Have Money Anymore to Live in Jakarta, But God Doesn't Sleep". The purpose of this study was to find out the use of touch maxim adherence in Deddy Corbuzier's podcast. The research method used is the Literature study method, the source of data in this study, namely the Deddy Corbuzier podcast video. Data collection techniques by means of reading techniques and note techniques. Based on the results of the discussion, it was found that there was the use of the maxim of politeness in language in Deddy Corbuzier's podcast there were the maxim of politeness of wisdom, maxim of praise/appreciation, maxim of humility, and maxim of agreement.